2019
DOI: 10.1016/j.idairyj.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cynara cardunculus L. flower from Alentejo as a coagulant agent for cheesemaking

Abstract: The cardoon (Cynara cardunculus L.) is a mandatory vegetable coagulant for certain Protected Designation of Origin Portuguese cheeses. It grows wild in Portugal and is used without any type of control regarding flower picking or extract preparation, representing some uncertainty in cheese manufacture. The variability in technological properties, in the context of traditional cheese manufacture, of cardoon flower ecotypes from the Alentejo region was evaluated, including milk clotting and proteolytic activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 24 publications
1
22
0
1
Order By: Relevance
“…In order to evaluate melon peels extracts as vegetable rennet, one important parameter that must be considered is the ratio of milk-clotting activity to proteolytic activity (MCA/PA). It is well-known that excessive proteolysis negatively affect coagulation force, as well as some, sensorial characteristics of the final products (Gomes et al, 2019). In turn, depending on the temperature MPJ showed an MCA/PA ratio of 995.34 ± 111.6 and 1485.84 ± 107.2 at temperatures of 80 and 85 • C, respectively.…”
Section: Melon By-products As Sources Of Proteolytic Enzymesmentioning
confidence: 97%
“…In order to evaluate melon peels extracts as vegetable rennet, one important parameter that must be considered is the ratio of milk-clotting activity to proteolytic activity (MCA/PA). It is well-known that excessive proteolysis negatively affect coagulation force, as well as some, sensorial characteristics of the final products (Gomes et al, 2019). In turn, depending on the temperature MPJ showed an MCA/PA ratio of 995.34 ± 111.6 and 1485.84 ± 107.2 at temperatures of 80 and 85 • C, respectively.…”
Section: Melon By-products As Sources Of Proteolytic Enzymesmentioning
confidence: 97%
“…Results of the characterization of extracts from the artichoke flowers were demonstrated by Gomes et al (2019) when studying extracts of 15 Cynara cardunculus L. flowers with proteolytic activity ranging from 4.10 to 5.28% and 3.63 to 5.07%. Lower values of the analyzes with extracts of the artichoke leaves were demonstrated by Llorente, Brutti and Caffini (2004) when determining the protein content (0.34, 0.28 and 0.13 mg/mL) and proteolytic activities (0.50, 2.39 and 1.10 U/mg) of the raw extracts of the artichoke leaves with use of electric mixer.…”
Section: Proteins Proteolytic and Specific Activity Of Artichoke Leaf Extractsmentioning
confidence: 99%
“…The evaluation of individual genotypes showed that the observed biodiversity is also reflected in the amount and type of APs present in the flowers of each genotype, with enzymes present in some genotypes and absent in others [16]. This variability was also found to affect the milk-clotting process, as the use of flower extracts from different thistle populations displayed different milk-clotting times, which ultimately affected cheese manufacturing and the rheological and sensorial characteristics of the final product [17,18]. Thus, the use of thistle flower extracts as milk-clotting agents is dependent upon the presence and specific activities of different APs.…”
Section: The Thistle Flower and The Impact Of Its Variability On Milkmentioning
confidence: 99%